AB0010 Lilrb3 expression on t cells correlates with disease activity in ra. (15th June 2017) - Holz, A; Witte, T; Schmidt, RE
Abstract : Background: Leukocyte immunoglobulin-like receptors (LILR) participate in the generation of immunological tolerance (1, 2). LILRB3 can be expressed on T cells and is an inhibiting receptor (3). Objectives: We wanted to study LILR expression on T cells in RA compared to SLE and controls. Methods: Heparinised human blood from blood donors was obtained from the Institute of Transfusion Medicine, Medical School Hannover (Germany). Blood samples from RA (DAS28 <3.2 n=11; DAS28>3.2 n=8) and SLE patients (n=9) were obtained from Outpatients` Clinic of the Department of Rheumatology and Immunology after informed consent. PBMCs were stained with LILRA2 (Biolegend, APC), LILRB3 (Biolegend, PE), CD3 (Biolegend, APC-Cy 7), CD4 (BD, PerCP-Cy5.5), CD8 (Biolegend, V500), CD25 (Biolegend, PE/Cy5), CD28 (Biolegend, Pacific Blue). Results were compared to isotype controls. Statistical analyses and figures were made with GraphPad Prism, ANOVA and the Mann-Whitney Test. Results: The percentage of both CD4+ and CD8+ T cells expressing LILRB3 was significantly higher in both inactive as well as active RA compared to controls or SLE (See Fig. 1 ) (p=0.0397 ANOVA: RA all vs. SLE vs. controls). Within the group of RA patients, the percentage of LILRB3 expressing T cells was highest in active compared to inactive (DAS28<3.2) RA (p=0.0287). LILRA2 was not expressed on T cells. Conclusions: Expression of LILRB3 correlates with disease activity of RA and is decreased after successful treatment with DMARDS or biologicals. Since LILRB3 is an inhibiting receptor the increased expression in active RA may be a counterregulation to reduce disease activity. References: Anderson KJ, Allen RL. Regulation of T-cell immunity by leucocyte immunoglobulin-like receptors: innate immune receptors for self on antigen-presenting cells. Immunology 2009 May;127(1):8–17. Thomas R, Matthias T, Witte T. Leukocyte immunoglobulin-like receptors as new players in autoimmunity. Clin Rev Allergy Immunol 2010 Apr;38(2–3):159–162. Brown D, Trowsdale J, Allen R. The LILR family: modulators of innate and adaptive immune pathways in health and disease. Tissue Antigens 2004 Sep;64(3):215–225. Acknowledgements: We thank the StrucMed program for the support, and Katja Kniesch for technical assistance. Disclosure of Interest: None declared